PENILAIAN SISTEM PENGADAAN BARANG/JASA PEMERINTAH REPUBLIC DEMOCRATICA DE TIMOR LESTE (RDTL) DENGAN MENGGUNAKAN RERANGKA OECD 2006 - , Oscar Sanches Faria, Dr. Mahfud Sholihin, M.Acc. Akt ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Public Procurementâs institution in Timor Leste is a major agent for public fund expenditure. Nearly, 70 -70.19 % of Timor Leste government funds are spent through the procurement every year.Therefore, the procurement should be managed properly in accordance with procurement regulations, guideline, and national and international standards which normally been used whole over the world. The RDTL government has sought to develop and improve the procurement system to prevent corruption, abuse of authority, project delays, and lack of transparency and does not limit the participation in tendering process. All of the effort is made in order to make procurement system runs efficiently, effectively, transparent, openness, competitive and fair or no discrimination. This study aims to assess the achievement of procurement objectives in the government of Timor Leste mainly: Directorate General of National Corporate Services, Department of National Procurement, Department of Inspection and Internal Audit, and Department of National Budget Execution at the Ministry of Finance. Besides it is also used at the Directorate General of National Procurement, Department of Logistics and State Assets at the Ministry of Infrastructure, last but not least at the Office of the National Procurement Commission. The qualitative method of case study was used in this research, and this method is used at the stage of data collection and data analysis. The study was conducted to assess the level of achievement for Timor Leste procurement system implementation in comparing with the OCEDâs framework (2006). The OECD is composing of: four pillars